Attenuation of hypertension by C-fiber stimulation of the human median nerve and the concept-based novel device. Issue 1 (December 2018) - Bang, Se; Ryu, Yeonhee; Chang, Suchan; Im, Chae; Bae, Jong; Gwak, Young; Yang, Chae; Kim, Hee
Abstract High blood pressure (BP) is a highly controllable risk factor for cardiovascular diseases; however, awareness of this condition and the rates of controlled hypertension are low. Experimental animal studies have shown that stimulation of the median nerve or PC6 acupoint over the wrist has effects on cardiovascular activities, including reductions in systolic and diastolic BPs. A proof-of-concept study was conducted in humans to investigate whether stimulation of median nerve near PC6 acupoint decreased high BP, identify the optimal stimulation parameters for the BP-lowering effects of median nerve stimulation, and determine the specific peripheral nerves or types of afferent fibers mediating the BP-lowering effects. Median nerve stimulation was carried out bilaterally or unilaterally with different stimulation parameters, and the BP and heart rate were monitored. The afferent mechanisms underlying the effects of median nerve stimulation on hypertension were investigated via microneurography, A-fiber blocking experiments, and localized chemical or electrical stimulation. Bilateral median nerve stimulation at either low or high frequencies produced profound but transient reductions in systolic BP, which were elicited when median nerve stimulation was unilaterally applied at interelectrode distances of 2 and 4 cm. Systolic BP was also reduced by electrical stimulation of the thumb on the palm side. Although microneurographic recordings revealed the excitation of both A- and C-fibers following median nerve stimulation, the median nerve-mediated reductions in BP were not affected by A-fiber blockade, and they were mimicked by the activation of C-fibers with capsaicin. The present results indicate that activation of C-fibers in the median nerve generates BP-lowering effects in humans. Based on our clinical study, an optimized median nerve stimulator was built and combined with a wrist BP monitor for simultaneous BP measurements and median nerve stimulation.